Knowledge and Attitude Regarding Pubertal Changes among Secondary Level Students of Selected Schools of Dhulikhel Municipality - Shrestha, S.; Neupane, B. (Kathmandu University Medical Journal, 2020)
Background Adolescence is a transition phase of life during which a lot of pubertal changes occur. If not dealt properly, many mental and behavioral disturbances can result. Adolescents must have good knowledge and attitude regarding physical and psychosocial pubertal changes. Objective To assess the knowledge and attitude regarding pubertal changes among secondary level students of selected school of Dhulikhel Municipality. Method A quantitative, descriptive cross-sectional study was conducted among secondary level students of Dhulikhel Municipality. Study was conducted among students of grade 9 and 10 of four government and three private schools of municipality. After selection of seven schools, proportionate stratified random sampling technique was done followed by lottery method to select required number of students. Both descriptive statistics and inferential statistics were applied using Statistical Package for Social Science (SPSS) Version 25.0 for data analysis. Result The mean score of knowledge regarding pubertal changes was 26.2±2.9. Likewise, the mean attitude score regarding pubertal changes was 55.4±1.2. Knowledge regarding pubertal change was significantly higher among age group 15-17 years. Females had higher knowledge compared to males. Attitude related to pubertal change was significantly more in respondents who studied in government school. Conclusion Adolescents of Dhulikhel municipality schools had good knowledge and attitude about pubertal changes.